DAMPAK DESENTRALISASI FISKAL TERHADAP OUTCOMES PELAYANAN PUBLIK BIDANG PENDIDIKAN (STUDI KASUS: PROVINSI JAWA TENGAH) - Solechah - (Value Added : Majalah Ekonomi dan Bisnis, 2013)
Fiscal decentralization was held since 2001 is purpose to give more capacity of public service that government do for people. Implementation of the regional autonomy through fiscal decentralization is expected to improve the quality of public services. This research is purpose to see the effect of fiscal decentralization to outcomes of public service in education sector. Education Outcomes is one measure that can be used to view the quality of public services. This research use panel data from ten residence and city in Central Java in 2007 until 209. The method to get the result of this research is use regression analysis approach to find the effect of fiscal decentralization to output and outcome of education sector of public service. The result of this research shows that fiscal decentralization have effect for outcome of education sector of public service. Fiscal decentralization has negatif effect and no significant to school participation rate. If fiscal decentralization increase one percent school participation rate down up to 2.364 and then pupil and teacher ratio has positif effect for school participatian rate, if pupil and teacher ratio increase one percent school participation rate rise up to 1.427, but Gross Regional Domestic Product percapita has positif effect and significant for school participation rate, if Gross Regional Domestic Product percapita increase one percent school participation rate rise up to 3.563.